PENGARUH CURRENT RATIO, RETURN ON ASSET DAN DEBT TO EQUITY TERHADAP PRICE BOOK VALUE (Studi kasus pada perusahaan food and beverage yang terdaftar di Bursa Efek Indonesia tahun 2016-2020) - Eni Widiya W; Nur Indah F; Tiffany Olivia H; Abd Rosyid; Zein Yasir (Nusantara Hasana Journal, 2023)
This study aims to examine the effect of CR, ROA, DER on PBV. The research sampling technique is a method with a purposive sampling technique where there are criteria for the population being sampled. The research sample is a food and beverage company listed on the Indonesia Stock Exchange (IDX). The companies listed on the Indonesia Stock Exchange during the 2016-2020 period consisted of 30 companies, with a total final sample of 40 during the 5 year research period. Data analysis techniques using the Estimate Test Model, Classic Assumption Test, Multiple Linear Using secondary regression data using Stata. The research findings show that (1) CR has a significant effect on PBV, (2) ROA has a significant effect on PBV, (3) DER has a significant effect on PBV.